Built environment characteristics and its association between physical performance, falls risk and functional mobility among Malaysian older adults - Devinder Kaur Ajit Singh; Yaksotha Palaniappan; Lam, Shu Zen; Azianah Ibrahim; Suzana Shahar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Older adults who walk in their neighbourhood with greater street connectivity are reported to have lower limb physical performance decline. There is limited information regarding the association between built environment characteristics and physical performance in older adults. The aim of this study was to examine the association between built environment characteristics, physical performance, falls risk and functional mobility among older adults. Sixty four (27 men and 37 women) community dwelling older adults aged 60 years and above (mean 67.4 ± 7.1 years) from senior citizen clubs in Kuala Lumpur, Malaysia participated in this cross-sectional study. Built environment characteristics were assessed using an adapted Neighbourhood Environment Walkability Scale (NEWS). Physical performance and falls risk was measured using Short Physical Performance Battery (SPPB) and Profile Physiological Profile Assessment (PPA) respectively. Timed Up and Go (TUG) and gait speed tests were used to assess functional mobility. There was a significant correlation between built environment and physical performance (r = 0.43, p < 0.001) and functional mobility measured using gait speed test (r = 0.27, p < 0.05) among older adults. Built environment was identified as a significant determinant of physical performance (R2 = 0.19, p < 0.001). Built environment characteristics is an important external factor in preserving physical performance in older adults. Programmes and policies for a more favourable built environment characteristics in the neighbourhoods should be encouraged to promote and maintain physical performance among older adults.